Creative nonfiction a manual for Filipino writers - Hidalgo, Cristina Pantoja (Quezon City University of the Philippines Press, 2003)
Contents: Creative nonfiction in the Philippines. Strategies of creative nonfiction writings. Types of creative nonfiction. Short concluding chapter.
Purpose: "It is designed to be a textbook for creative writing. It is intended for students taking courses in creative nonfiction."
Keywords: Reportage literature -- Handbooks, manuals, etc; Exposition (Rhetoric).; Feature writing -- Handbooks, manuals, etc; Journalism -- Handbooks, manuals, etc